(untitled) (Вісник: Міжнародні відносини, 2025)
The COVID-19 pandemic, the war in Ukraine, energy crises, and geopolitical instability have exposed the vulnerabilities of the EU internal market. Unilateral measures by Member States, such as export restrictions and transit blockades, have disrupted supply chains and challenged the free movement of goods and services. In response, the EU adopted Regulation (EU) 2024/2747 (Internal Market Emergency and Resilience Act, IMERA), which establishes a crisis management framework aimed at minimizing market fragmentation, ensuring the continuity of trade, and limiting national interventions during emergencies. The regulation introduces three response levels: preparedness mode, vigilance mode, and emergency mode, along with a centralized coordination mechanism for Member States’ actions. A key provision is the prohibition of unilateral national restrictions within the internal market (Article 7 IMERA), which mitigates risks related to export bans, supply chain disruptions, and discriminatory measures. The research methodology includes the analysis of EU legislative acts, a comparative legal approach, and an assessment of IMERA’s practical implications. The study evaluates the regulation’s impact on internal market functioning, trade policy coordination, and crisis response mechanisms. Conclusions indicate that IMERA serves as a strategic tool for maintaining the continuous operation of the EU internal market during crises. The regulation prevents uncontrolled national interventions, ensures policy coherence among Member States, and strengthens the stability of supply chains within the EU. The introduction of priority-rated requests for economic operators and joint procurement mechanisms enhances the EU’s preparedness for future crises. Additionally, provisions on energy security and strategic resource management reinforce market resilience. Although primarily designed for the EU internal market, the regulation will have indirect implications for external trade partners, such as Ukraine, which is integrated into European supply chains. The restriction of national trade barriers within the EU ensures stable access to critical goods and creates more predictable conditions for external economic actors. Further research should focus on assessing IMERA’s enforcement effectiveness and its long-term impact on crisis governance in the EU.